Media and Disability in Kenya - Njogu, Kimani (Disability Studies Quarterly, 2009)
Persons with disabilities (PWD) in Kenya become involved with the media for a wide range of reasons, including as reporters or activists challenging attitudes, practices, and policies, and to urge for a better representation of themselves and of their experiences. They may also be presented as newsmakers, such as in the case of the award-winning Kenyan athlete, Henry Wanyoike, who has won numerous medals despite his visual disability. In spite of these presences, media in Kenya have a long way to go in order to represent persons with disability in their completeness. Most media present persons with disabilities as objects of pity whose accomplishments must be held in awe. Yet the industry can play a central role in attitude and policy change at household, community, and national levels. In this article, we will consider ways in which media in Kenya can play a positive role in bringing to the fore disability issues, facilitating pro-disability behaviour, and ensuring the implementation of policies that protect the rights of people with disabilities.